The Impact Of Environmental, Social and Governance on Corporate Value: The Role Of Real Earning Management As Moderating Variable - Adlah, Adzhana; Febrianto, Rahmat (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2023)
The purpose of this study is to provide empirical evidence on the influence of Environmental, Social, and Governance (ESG) on corporate value. The study also examined the role of real earnings management (REM) as a moderation variable in the relationship. Our sample is non-financial companies listed on the Indonesia Stock Exchange for the period 2012-2020. Tobin’s Q is used to measure the value of a company. ESG is measured using ESG scores issued by Thomson Reuters. REM is calculated by combining abnormal cash flow calculations, abnormal manufacturing costs, and abnormal discretionary costs. The results of statistical testing show that ESG affects the value of the company. The results of this study support the findings of previous literature, which empirically found that ESG practices can increase company value because investors have assumed that ESG is a relevant value in decision-making. In addition, statistical results also show that REM is not proven to have a moderating effect on the effect of ESG on company value, but REM has an influence on company value. The results of this study support the findings of previous literature, which empirically found that REM practices carried out by companies will reduce company value if detected by investors. The study had some limitations. First, this study only uses ESG data provided by Thomson Reuters with minimal data completeness, so it does not adequately cover the data needed. Second, the study only focused on the non-financial sector.